Basic Pencak Silat Techniques for Athletes - Suyudi, Imam; Ishak, Muhammad (Sains Global Institut, Indonesia, 2024)
This study aims to determine the level of basic pencak silat techniques in Bantaeng Regency athletes. This research is a type of descriptive research. The population of this study were all Pencaksilat athletes from Bantaeng Regency with a total research sample of 25 male athletes selected by random sampling. The data analysis technique used is a descriptive percentage analysis technique using the SPSS version 21.00 data processing system. Based on the results of data analysis, this research concludes that the basic techniques for pencak silat athletes in Bantaeng Regency are as follows: the number of pencak silat athletes is 25 people with 24 people in the good category (96.0%) and 1 person in the medium category (4.0 %). And there are no athletes who have the categories very good, poor or very poor. Thus it can be concluded that the basic techniques of pencak silat athletes in Bantaeng Regency are categorized as good.